The permian end catastrophe: an evidence for a broader phenomenon - Meth, Sergio (Ciência e Natura, 2020)
It is well known that about 250 million years ago a huge catastrophe took place in our planet, with effects so big that about 95 % of the species disappeared in the process including sea animals. This event is called “the Permian extinction”. Other effects are also apparently connected to this event. This kind of event would require an extremely huge amount of energy. Since there is no evidence for an asteroid impact, the energy source should be searched inside the planet. Most importantly, it should show an energy source capable of producing such huge phenomenon. The aim of this paper is to propose a model to explain this extinction event and to show that there is evidence that this is a phenomenon that apparently happened several times not only in our planet but also in other Solar System bodies.